Rencana Bisnis Pengembangan Usaha Jasa AKI Kendaraan Berbasis Sistem Informasi - Desyana, Desyana; Suwandi, Suwandi (Journal of Entrepreneurship, Management and Industry (JEMI), 2018)
This final assignment journal contains summary of the Babal Aki business plan about the development of e-commerce system with an online store and smartphone applications, resellers system, and manufacturing cooperation to make their own brands. This journal explained a few things about the current business processes of Babal Aki and the development plans for the next 5 years.The analysis conducted includes analysis of the marketing mix, SWOT, Blue Ocean Strategy, competitors, and also the Business Model Canvas. In its development plan, it also contained some information relating to the financial of Babal Aki, as well as information on funding, profit and loss, and balance sheets of Babal Aki.